Electoral strategies against security. Comments on campaign positioning. Buenos Aires (2007) (2020)
The topics of urban insecurity have advanced as a central part of the local electoral strategies in the recent years. The objective of this paper is to analyze the political strategies in dispute based on the problem of urban crime. The approach is qualitatively based on the technique of political discourse analysis. The fragments referring to the issue of urban security are analyzed within a corpus of campaign material (graphic, audiovisual and journalistic) in the election for Head of Government of the city of Buenos Aires, Argentina, in 2007. The results show how most political spaces incorporated urban security and defined their electoral positions based on this topic. The speeches of each political space focus on the modalities that differentiate the way of intervening on the criminal issue. Thus, it was verified that the speech of the PRO used descriptive components with diagnostic and proactive elements (the city is risky and with the measures that will be taken the situation could be resolved), the FPV highlighted the evasive key of the security issue to focus on the social topics, and +BA reinforced the prescriptive component (it should continue like this). The components used by each candidate form a recipient that defines a differential us in each case: the victim citizen; the rational citizen and the protected citizen.